Balancing Tradition and Innovation: Curriculum Integration, Digital Competence, and Islamic Identity in Indonesian Pesantren - Muhammad Rehan Sabir; Abdam Yusif; Alwy Ahmed Mohamed (Solo Universal Journal of Islamic Education and Multiculturalism, 2026)
Objective: This study aims to analyze how Islamic boarding schools (pesantren) in Indonesia formulate and implement strategies for integrating curriculum reform, digital competence, and Islamic identity in response to contemporary educational modernization. Theoretical framework: The study is grounded in Homi Bhabha’s Cultural Hybridization Theory, which explains the negotiation between tradition and modernity, and the Technological Pedagogical Content Knowledge (TPACK) Framework, which emphasizes the effective integration of technology, pedagogy, and content knowledge in educational practice. Literature review: The literature review highlights ongoing debates concerning pesantren modernization, curriculum integration, digital transformation, state educational policies, and the preservation of Islamic authenticity. Methods: This research employs a qualitative case study approach involving three pesantren in Java representing urban, semi-urban, and rural contexts. Data were collected through semi-structured interviews with kyai, teachers, and students, classroom observations, document analysis, and triangulated qualitative coding using NVivo. Results: The findings reveal three distinct modernization patterns: full integration, hybrid integration, and traditional resistance. Urban pesantren demonstrate successful incorporation of STEM, ICT, and digital learning platforms while maintaining religious commitments. Semi-urban pesantren adopt selective hybrid models, whereas rural pesantren tend to resist technological integration due to concerns regarding cultural and spiritual erosion. Leadership orientation, institutional readiness, teacher competence, and infrastructure availability emerge as critical factors influencing modernization outcomes. The study further identifies digital tools such as WhatsApp, Google Meet, Maktabah Syamilah, and Moodle as important instruments supporting educational innovation. Implications: The implications suggest that modernization and Islamic authenticity are not mutually exclusive but can be harmonized through balanced educational reform, adaptive leadership, and context-sensitive policies. Novelty: The novelty of this study lies in proposing an integrative strategic model that simultaneously combines curriculum integration, digital competence, and Islamic identity within a single analytical framework, offering a practical pathway for sustainable pesantren modernization while preserving religious and cultural values.